Salidroside Ameliorates Depression by Suppressing NLRP3-Mediated Pyroptosis via P2X7/NF-κB/NLRP3 Signaling Pathway - Chai, Yuhui; Cai, Yawen; Fu, Yu; Wang, Yingdi; Zhang, Yiming; Zhang, Xue; Zhu, Lingpeng; Miao, Mingxing; Yan, Tianhua (Frontiers in Pharmacology, 2022)
Depression is a common and serious mental disorder. Data on its pathogenesis remain unclear and the options of drug treatments are limited. Here, we explored the role of pyroptosis, a novel pro-inflammatory programmed cell death process, in depression as well as the anti-depression effects and mechanisms of salidroside (Sal), a bioactive extract from Rhodiola rosea L. We established a corticosterone (CORT)-induced or lipopolysaccharide (LPS)-induced mice in vivo, and CORT, or nigericin (NLRP3 agonist)-induced PC12 cells in vitro. Our findings demonstrated that Sal profoundly mediated CORT or LPS-induced depressive behavior and improved synaptic plasticity by upregulating the expression of brain-derived neurotrophic factor (BDNF) gene. The data showed upregulation of proteins associated with NLRP3-mediated pyroptosis, including NLRP3, cleaved Caspase-1, IL-1β, IL-18, and cleaved GSDMD. The molecular docking simulation predicted that Sal would interact with P2X7 of the P2X7/NF-κB/NLRP3 signaling pathway. In addition, our findings showed that the NLRP3-mediated pyroptosis was regulated by P2X7/NF-κB/NLRP3 signaling pathway. Interestingly, Sal was shown to ameliorate depression via suppression of the P2X7/NF-κB/NLRP3 mediated pyroptosis, and rescued nigericin-induced pyroptosis in the PC12 cells. Besides, knock down of the NLRP3 gene by siRNA markedly increased the inhibitory effects of Sal on pyroptosis and proinflammatory responses. Taken together, our findings demonstrated that pyroptosis plays a crucial role in depression, and Sal ameliorates depression by suppressing the P2X7/NF-κB/NLRP3-mediated pyroptosis. Thus, our study provides new insights into the potential treatment options for depression.